Tiny Regulators of Massive Tissue: MicroRNAs in Skeletal Muscle Development, Myopathies, and Cancer Cachexia - Singh, Gurinder Bir; Cowan, Douglas B; Wang, Da-Zhi (Frontiers in Oncology, 2020)
Skeletal muscles are the largest tissues in our body and the physiological function of muscle is essential to every aspect of life. The regulation of development, homeostasis, and metabolism is critical for the proper functioning of skeletal muscle. Consequently, understanding the processes involved in the regulation of myogenesis is of great interest. Non-coding RNAs especially microRNAs (miRNAs) are important regulators of gene expression and function. MiRNAs are small (~22 nucleotides long) noncoding RNAs known to negatively regulate target gene expression post-transcriptionally and are abundantly expressed in skeletal muscle. Gain- and loss-of function studies have revealed important roles of this class of small molecules in muscle biology and disease. In this review, we summarize the latest research that explores the role of miRNAs in skeletal muscle development, gene expression, and function as well as in muscle disorders like sarcopenia and Duchenne muscular dystrophy (DMD). Continuing with the theme of the current review series, we also briefly discuss the role of miRNAs in cancer cachexia.